2020
DOI: 10.1007/s00586-020-06423-6
|View full text |Cite
|
Sign up to set email alerts
|

Does pre-operative multifidus morphology on MRI predict clinical outcomes in adults following surgical treatment for degenerative lumbar spine disease? A systematic review

Abstract: Aim Low back pain (LBP) resulting from degenerative lumbar spine disease is a leading contributor to global disability. Changes in the morphology of the lumbar multifidus muscle on magnetic-resonance imaging (MRI) are associated with worse LBP and disability, but the association between multifidus morphology and post-operative outcomes is not known. The purpose of this systematic review is to examine the relationship between pre-operative multifidus morphology and postoperative changes in pain and disability. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
4
17
1
Order By: Relevance
“…For abating the effect of heterogeneity, we conducted subgroup analyses in each complication according to measured paraspinal muscles and its method of morphology measure. Similar subgroup analyses were performed by previous studies [14,19]. We defined the paraspinal extensor muscle (PSE) group as the integrity of MF and ES.…”
Section: Synthesis Of Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For abating the effect of heterogeneity, we conducted subgroup analyses in each complication according to measured paraspinal muscles and its method of morphology measure. Similar subgroup analyses were performed by previous studies [14,19]. We defined the paraspinal extensor muscle (PSE) group as the integrity of MF and ES.…”
Section: Synthesis Of Resultsmentioning
confidence: 93%
“…Although substantial work has been carried out to identify potential factors for spine surgery prognosis [11,12], few unequivocal predictive factors related with paraspinal muscle have come to light. Some reviews previously concluded the degree of preoperative paraspinal muscle degeneration in relation to disability and persistent pain after surgery [13,14], whereas no review has focused on the predictive value of paraspinal muscles on complications.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies between ratings of the investigators were resolved by consensus. Each study was then given an overall rating based on a method reported by Jermy et al, whereby low bias studies have ≤2 domains rated as moderate with the remainder rated low; moderate bias studies have either 3 moderate ratings or one moderate and one high with the remainder rated low; and high bias studies having either ≥2 moderate plus one high rating, or ≥2 high ratings, or ≥4 of moderate ratings for each domain (35).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Low, moderate, and high refer to the level of risk of bias for each domain, for each study. Overall Rating Scoring System(35): Low risk: Up to 2 moderate ratings with remainder low. Moderate risk: 3 low + 3 moderate OR 1 moderate + 1 high.…”
mentioning
confidence: 99%
“…Fortin et al clarified that the morphology and fatty infiltration of the multifidus and psoas is associated with patients’ functional status and symptoms [ 5 ]. Jermy et al found a trend for better outcomes following surgery if pre-operative multifidus quality is better [ 6 ].…”
Section: Introductionmentioning
confidence: 99%